Case report: Presumptive subcutaneous malignant peripheral nerve sheath tumor with intracranial invasion and osteolysis in the posterior fossa of a dog - Hidari, Kyosuke; Nakamoto, Yuya; Sakurai, Keiichi; Sakurai, Yoko; Nibe, Kazumi; Nakamoto, Miwa (Frontiers in Veterinary Science, 2022)
A 13-year-old castrated male Toy Poodle presented with an acute vestibular disorder. Magnetic resonance imaging and computed tomography revealed a large oval space-occupying mass with skull destruction located from the subcutaneous tissue to the posterior fossa region. Histopathologically, the mass was a bundled growth of spindle-shaped mesenchymal tumor cells between the myofibrillar and collagen bundles. The cells were moderately irregular in size and had eosinophilic stained cytoplasm. The cells were highly atypical and had rare mitotic figures. Neoplastic cells were immunoreactive for S100, GFAP, Olig-2, SOX10 and immunonegative for NF, E-cadherin, and Claudin-1. Collective findings were presumptive with a diagnosis of malignant peripheral nerve sheath tumor.